The Effect of Reward and Punishment on Employee Performance with Work Discipline as Intervening Variable at PT BPRS Niaga Madani - Amalia, Andi Rezky Ananda; Maupa, Haris; Jusni (Economics and Business Journal (ECBIS), 2023)
The development of a company heavily relies on qualified human resources. The level of employee performance can reveal the quality of human resources in achieving company goals. One of the factors that can enhance employee performance is work discipline. A common strategy used by companies to improve employee performance is by providing rewards and punishments. This research aims to analyze the influence of rewards and punishments on employee performance through work discipline at PT BPRS Niaga Madani. The sample for this study consisted of 47 respondents. This research adopts a quantitative approach, collecting data through interviews, questionnaires, and documentation. The data analysis process in this study employs path analysis. The results of this research show that rewards do not have a significant effect on work discipline, and they also do not significantly influence employee performance. On the other hand, punishments significantly affect work discipline and employee performance. Work discipline, in turn, significantly affects employee performance. Rewards, directly and indirectly, affect employee performance through work discipline, while punishments have both direct and indirect effects